The Changes from Suntiang Pasumandan to Suntiang Panari at the Tuah Sakato Art Studio - Idha, Muhammad Trio; Efi, Agusti (Universitas Jambi, Indonesia, 2024)
This research aimed to describe the form of Suntiang Pasumandan, analyze changes in the function of Suntiang Pasumandan into Suntiang Panari (dancers) at Tuah Sakato Art Studio, analyzing the types of materials used in making Suntiang Pasumandan and Suntiang Penari at Tuah Sakato Art Studio. This research was qualitative. In collecting the data, the researchers used observation, interviews, documents, and literature studies. The steps of analyzing data were data reduction, data presentation, data verification, and conclusions. The results showed that the changes from Suntiang Pasumandan to Suntiang Panari at Tuah Sakato Art Studio came from two aspects. The first aspect was commercial needs. It was about whether the dancers' headdresses were good at Tuah Sakato Art Studio. The second aspect was the change in the function of use. Suntiang Pasumandan was used in cultural activities as a headdress in traditional marriage processions, supported by the rules that apply in the traditional procession.